Pelatihan Merancang Pembelajaran Online Berbasis E-Learning Bagi Guru dan Calon Guru - Magdalena Wangge (Jurnal Nasional Pengabdian Masyarakat, 2021)
One form of application of information and communication technology in the field of education and the requisitedue to the current pandemic situation is the application of online learning or E-learning-based online learning.The purpose of this community service activity is to assist teachers and prospective teachers in designing Elearning-based online learning with various media of information and communication technology that they aregood at. This service activity is carried out in the form of a webinar and is attended by more than 300participants. The method used in this research is the method of observation, guidance, and training, discussion,and evaluation. In designing e-learning-based online learning, teachers and prospective teachers need to payattention to the following: understanding about e-learning, identifying the characteristics of each student,designing and developing interactive material, implementing appropriate teaching strategies in deliveringmaterial electronically, organize material well so that it is easy for students to learn, take part in various onlinetraining that is held for example webinars to increase knowledge and skills in designing e-learning, involveyourself in every stage from planning, developing, to making decisions, and evaluating learning, both from theteacher's perceptions or from their students